Boards: Independent and Committed Directors? - Pascal Gantenbein; Christophe Volonté (University of Basel, Center of Business and Economics (WWZ), 2011)
Regulators and shareholders are calling for independent directors. Independent directors, however, have numerous external professional commitments. Using To- bin's Q as an approximation of market valuation and controlling for endogeneity, our empirical analysis reveals that neither external commitments are negatively related to firm performance nor is independence positively related to it. However, more precise analyses show that executive directors and family representatives have a positive relationship with Tobin's Q. In contrast, external executives are negatively correlated with firm valuation. Moreover, the study indicates that the frequency and duration of meetings are negatively affected by the fraction of executive directors on the board. Insiders potentially reduce the need for meetings because of their specialist competence. The results invalidate rules advocating independent directors and oppose the engagement of directors with external commitments.
Keywords: G30; G34; K22; 330; Corporate governance: Board of directors; Board independence; Board busyness; External commitments; Corporate Governance; Board of Directors; Eigentümerstruktur; Unternehmenswert; Tobins Q; Schweiz